PENGEMASAN PESAN PARIWISATA BUDAYA PADA AKUN INSTAGRAM @KARISMAEVENTNUSANTARA : (Analisis Isi Kualitatif Pada Konten Promosi Event Periode Januari Hingga Desember 2023) - Safira Rizky Amalia; Algooth Putranto (Jurnal Komunikasi & Media Digital, 2024)
Cultural tourism has become a hot topic in raising the issue of cultural preservation amid globalization. The utilization of Instagram to display cultural tourism messages is an effective effort implemented by the Ministry of Tourism and Creative Economy through the @karismaeventnusantara account. So this research has a problem formulation related to how to package cultural tourism messages in event promotion content on the @karismaeventnusantara Instagram account from January to December 2023. To describe the presentation of cultural tourism message packaging designed for each post. The method used is qualitative content analysis with descriptive type. Determination of content as a unit of analysis is limited to the period range during 2023. The results show that message packaging is dominated by informative message forms, reinforced by the theme of traditional events using video reel content forms with the presentation of information and inspiration types. Interestingly, it is not presented in the concept of entertainment but to highlight the cultural message of tradition.